Evaluation of the Diagnostic Accuracy of Superparamagnetic Iron Oxide Nanoparticles on Breast Cancer: A Systematic Review and Meta-analysis - Yan Chen; Baiyun Sun; Cicilia Marcella (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: The present study was conducted to evaluate the diagnostic accuracy of Superparamagnetic iron oxide nanoparticles in breast cancer.Material and methods: We examined all international databases, including PubMed, Scopus, Science Direct, ISI, Web of Knowledge, and Embase, searching until January 2023 based on keywords related to the objectives of the study. Based on the PRISMA 2020 checklist, the current study was conducted, and the Google Scholar search engine was also used to find related articles. A fixed-effect model and inverse-variance method were used to calculate the 95% confidence interval risk ratio. The meta-analysis was conducted using Stata/MP v. 17 software.Results: The abstracts of 477 articles were reviewed, and 51 articles were selected for full-text review, of which 15 articles were included in the meta-analysis. The risk ratio of patient detection rate between superparamagnetic iron oxide nanoparticles and the standard method was 1.02 (RR, 1.02 95% CI 0.52, 1.53; p>0.05). Compared to the control group, the superparamagnetic iron oxide nanoparticles group showed a higher superiority in extracting more SLN (RR, 1.07 95% CI 0.52, 1.61; p<0.05).Conclusions: Based on the findings of the present meta-analysis, superparamagnetic iron oxide nanoparticles can be a suitable alternative to standard methods in sentinel lymph node detection in breast cancer patients. It is suggested to study larger populations to confirm the present evidence.